Penerapan Akad Murabahah dalam Pembiayaan bagi Nasabah Inklusif di BTPN Syariah - Setiawan, Mohammad Irvan; Oktafia, Renny; Nisa, Fauzatul Laily (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The existence of Islamic banking in the midst of Indonesian community activities is one of the options in carrying out economic activities, Islamic banks that operate according to Islamic principles. One of the Islamic banks in Indonesia is Bank BTPN Syariah, in the financial sector carried out by BTPN Syariah there is one financing product that uses a murabahah contract. The agreement in question is the same as the sale and purchase contract. The financing carried out by BTPN Syariah is intended for inclusive customers who are underprivileged mothers who have not been touched by banks, so BTPN Syariah's role here is to provide financing and training in developing its customers' businesses. The method used in this study is a qualitative research method by conducting interviews and observations. Based on the results of the research that has been conducted, it is known that the application of murabahah contracts in financing at BTPN Syariah is also carried out with Wakalah contracts so that the purchase of goods is not carried out directly by the bank, but the purchase of goods is represented to the customer by the bank. So that the financing carried out by BTPN Syariah does not fully use a murabahah contract, but becomes a wakalah wal murabahah contract on "Tepat Pembiayaan Syariah" financing product. Keywords: BTPN Syariah, Financing, Murabahah Contract